2018
DOI: 10.1021/acs.chemrestox.7b00314
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Cyanide-Scavenging Capabilities of Some Cobalt-Containing Complexes in Mice

Abstract: Four cobalt-containing macrocyclic compounds previously shown to ameliorate cyanide toxicity have been comparatively evaluated with an acute sublethal toxicity model in conscious (unanesthetized) adult male Swiss-Webster mice. All of the compounds (the cobalt-corrins cobalamin and cobinamide, a cobalt-porphyrin, plus a cobalt-Schiff base macrocycle) given 5 min prior to the toxicant dose significantly decreased the righting-recovery time of cyanide-intoxicated mice, but the doses required for maximal antidotal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…The protective effect of CoN 4 [11.3.1] against cyanide toxicity has previously been demonstrated in a mouse model. 12,13 When CoN 4 [11.3.1]Br 2 (37 mg/kg) was given at 5 min post sodium azide, all the mice recovered, the majority did not knockdown (71%), and those that did (29%) recovered by 12 min (Table 1). These results clearly demonstrate that CoN 4 [11.3.1] is a potential antidote to azide toxicity, providing encouragement for the further development of scavenger-based therapeutics.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The protective effect of CoN 4 [11.3.1] against cyanide toxicity has previously been demonstrated in a mouse model. 12,13 When CoN 4 [11.3.1]Br 2 (37 mg/kg) was given at 5 min post sodium azide, all the mice recovered, the majority did not knockdown (71%), and those that did (29%) recovered by 12 min (Table 1). These results clearly demonstrate that CoN 4 [11.3.1] is a potential antidote to azide toxicity, providing encouragement for the further development of scavenger-based therapeutics.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The detoxification of cyanide by cobalt complexes has recently been suggested to consist of the toxicant binding to the reduced (substitution labile) Co­(II) forms, resulting in lowering of their oxidation potentials; this in turn facilitates oxidation to the (substitution inert) Co­(III) cyanide adducts that may then be excreted. , That is, bound cyanide becomes trapped in kinetically stable forms from which it is slow to dissociate, preventing systemic redistribution of the toxicant and, thereby, nullifying its toxicity . A somewhat similar mechanism of decorporation is plausibly operating in the case of the current preliminary experiments with azide intoxicated mice given Co­(II)­N 4 [11.3.1] (Table ) but differing in detail.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cobinamide is a cobalamin derivative, which has the advantage of allowing two CNs to bind to the cobalt ion of the Corrine ring . Cobinamide is 3-10 times more potent than hydroxocobalamin in mouse, rabbit, and swine models (Chan et al, 2015;Chan et al, 2018;Cronican et al, 2018). It is reported that nitrocobinamide derivatives are very stable and are absorbed well after IM injection (Chan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%